2000
DOI: 10.1192/bjp.176.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Trends in special (high-security) hospitals

Abstract: There is continuing demand from all parts of the country for high-security hospital beds. The smaller numbers admitted appear to include more demanding cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…However, due to inconsistencies in defining medium secure units, the authors are sceptical about the validity in comparing`real numbers' of women; some of the increase may be due to the exodus of women from special hospitals. However, what is clearer is that women currently occupy 19% of the beds in medium secure units, which suggests a 1:5 female/male ratio consistent with that of the special hospitals (Jamieson et al, 2000). The lack of clear governmental reporting of the`real numbers' and distribution of women in medium secure units has an impact on the management of these patients and the delegation of limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to inconsistencies in defining medium secure units, the authors are sceptical about the validity in comparing`real numbers' of women; some of the increase may be due to the exodus of women from special hospitals. However, what is clearer is that women currently occupy 19% of the beds in medium secure units, which suggests a 1:5 female/male ratio consistent with that of the special hospitals (Jamieson et al, 2000). The lack of clear governmental reporting of the`real numbers' and distribution of women in medium secure units has an impact on the management of these patients and the delegation of limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…screening services or referral routes); assessment; treatment; rehabilitation; continuing care (or transfer or discharge) (see also procedural security) Table 2 As in Table 2 patient workers according to in Table 2 Research has recently shown that fewer patients are admitted on civil sections to London's forensic services, and also that London has a higher proportion of restriction-order patients than do other regions of England (Coid et al, 2001b). At the same time, the numbers admitted to special hospitals are falling year on year (Jamieson et al, 2000). It appears that admission thresholds are drifting upwards in a responsive but unplanned manner, determined by availability of resources rather than any more objective criteria.…”
Section: Box 2 Mapping Modelsmentioning
confidence: 96%
“…A recent study by Jamieson (Jamieson et al, 2000) has confirmed the continuing demand for high security beds for adults. The authors highlighted that 'routes into special hospital have become more complex over time, with more admissions resulting from failed placements elsewhere'.…”
Section: Service Implicationsmentioning
confidence: 79%
“…The National Health Service Act 1977 for England and Wales requires the Secretary of State to provide high security hospitals for detained mentally disordered patients 'who in his opinion require treatment under conditions of special security on account of their dangerous, violent or criminal propensities'. Changes in their management and referral process have been described previously (Jamieson et al, 2000). As of April 2001, Broadmoor and Rampton merged with other NHS trusts, to form the West London Mental Health NHS Tr ust and Nottinghamshire Healthcare NHS Trust respectively.…”
Section: Introductionmentioning
confidence: 97%